The Role Of Friendship In Character Development: Lessons From The Biblical Story Of David And Jonathan - Janes Sinaga; Ramlen Woran; Juita Lusiana Sinambela (Berumpun: International Journal of Social, Politics, and Humanities, 2022)
Amidst the complexities of modern life, the role of friendship in character development is becoming increasingly important. The presence of true friends not only provides emotional support, but also serves as a mirror for self-knowledge. This study aims to explore the role of friendship in character development based on the story of David and Jonathan in the Bible. A qualitative approach with case studies is used to analyze narratives that are relevant to the friendship between the two characters. The results of the study show that deep friendship has a major positive influence in shaping individual character. Loyalty, emotional support, and inspiration from true friends lay a solid foundation for the development of strong and meaningful character. The story of Daud and Jonathan emphasizes the importance of friendship values in facing life's challenges, forming self-identities, and achieving full potential. This research also underscores the relevance of friendship values in modern life, inviting us to build supportive and inspiring friendships in order to build quality and integrity characters. The findings in this study provide insight into how friendship can be a crucial aspect in shaping human character and provide inspiration for individuals to develop meaningful social relationships in everyday society.